Implementação de porta lógicas ópticas com acoplador direcional não linear triplo planar simétrico de fibras ópticas - Menezes, José Wally Mendonça (2006)
In this work, optical logical gates are proposed starting from the use of a symmetric three-core nonlinear directional coupler (NLDC) of fiber optic and with one of the guides operating as control. For such end, we obtain the characteristics of transmission of the coupler and, soon afterwards, we made an analysis of the extinction ratio and of the compression factor. Initially, we investigated the acting of the proposed coupler operating in the regime CW and later using ultra short pulses, type sóliton with 2ps of width. With the model proposed for the device, we got to execute logical gates AND, NAND, OR, XOR and NOT for a group of applied phases to the control pulse. The logical gates generated with the device operating with signs CW, they came more efficient than the same gates generated with soliton pulses.